Ultrasound for the detection of full-thickness rotator cuff tears: the learning curve for an orthopaedic surgeon using a novel training method - Iossifidis, Anestis (Shoulder Elbow, 2014)
BACKGROUND: The present study aims to add to the body of evidence delineating the learning curve for a shoulder surgeon to become proficient in focussed ultrasound for the detection of full-thickness rotator cuff tears, as well as to describe a learning method for this skill. METHODS: Consecutive patients who were scheduled to undergo an arthroscopy for rotator cuff disease were scanned immediately before surgery by a senior shoulder surgeon with limited previous experience of shoulder ultrasound. The presence or absence of a full-thickness rotator cuff tear on scan was compared with intra-operative findings as the gold standard. RESULTS: Two hundred and ten shoulders were scanned over three equal learning periods. Comparing predictive values from the first to the third training period, sensitivity improved from 0.86 to 0.95, specificity from 0.92 to 0.98, negative predictive value from 0.94 to 0.98, and positive predictive value from 0.82 to 0.95. CONCLUSIONS: The high predictive values obtained in the present study for surgeon-led detection of cuff tears using ultrasound are comparable with those quoted for musculoskeletal radiologists in the literature. The present study adds evidence that a shoulder surgeon can achieve accelerated learning of this skill and offers some potentially time-saving and patient-friendly alternatives to existing guidelines.